Flight from safety: How a change to the deposit insurance limit affects households' portfolio allocation - Evren Damar; Reint Gropp; Adi Mordel (Bank of Canada, 2019)
We study how an increase to the deposit insurance limit affects households' portfolio allocation by exogenously increasing the share of safe financial assets. Using unique data that identify insured versus uninsured deposits, along with detailed information on Canadian households' portfolio holdings, we show that households respond by drawing down deposits and shifting towards mutual funds and stocks. These outflows amount to 2.8% of outstanding deposits in the banking system. The empirical evidence, consistent with a standard portfolio choice model that is modified to accommodate uninsured deposits, indicates that more generous deposit insurance coverage results in non-trivial adjustments to household portfolios.
Keywords: D14; G21; G28; L51; 330; Financial institutions; Financial system regulation and policies